Critical Perspectives on Climate Action in the Republic of North Macedonia - Brsakoska Bazerkoska, Julija; Stojkovski, Ljupcho (Institute for Human Rights & UNDP, 2024)
This work will shed light on the path of North Macedonia in meeting SDGs 13 and 16, on the normative requirements under these SDGs, and their interlinkage in this case. This is especially pertinent, since in almost all of the indicators that measure the progress in meeting SDG 13 and SDG 16 (related to good governance), the Republic of North Macedonia has been either “stagnating” or “decreasing” in the last year. Thus, at the conclusion of this work, some recommendations to address some of the shortcomings will also be provided.
Keywords: UN sustainable development goals; climate action